2012
DOI: 10.3329/bjpbg.v25i1.17010
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC DIVERSITY ANALYSIS IN RICE (Oryza sativa L.)

Abstract: The experiment was conducted under the agro-ecological zone of Modhupur Tract (AEZ-28) to determine the genetic diversity among 39 rice genotypes, collected from Bangladesh Rice Research Institute, Lal Teer Seed Ltd. and Chittagong Hill Tracts. The genotypes were grouped into six clusters based on Mahalanobis's D 2 statistics and Canonical Variate Analysis. Cluster I consisted with the highest number of (11) genotypes from different origin, whereas cluster IV consisted with the lowest number of (3) genotypes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
5
8
0
Order By: Relevance
“…The traits viz., number of filled grains per panicle, days to 50% flowering, and grain yield per plot, ear bearing tillers per m 2 contributed more than ninety per cent towards total divergence. The results were in conformity with [11,12,13]. Hence, these characters should be given importance during hybridization and selection in the segregating population under water stress condition.…”
Section: Resultssupporting
confidence: 88%
“…The traits viz., number of filled grains per panicle, days to 50% flowering, and grain yield per plot, ear bearing tillers per m 2 contributed more than ninety per cent towards total divergence. The results were in conformity with [11,12,13]. Hence, these characters should be given importance during hybridization and selection in the segregating population under water stress condition.…”
Section: Resultssupporting
confidence: 88%
“…A survey of recent literatures pertaining to our study revealed the formation of five clusters in the investigations by Siddique et al, (2013), (Kumar et al, 2014) involving 40 and 134 genotypes for 14 and 16 traits. Chakma et al, (2012), Ranjith et al, (2018), Singh et al, (2018) and Tiruneh et al, (2019) obtained six clusters with around same number of genotypes viz., 39, 30, 30 and 36 for 12, 12, 14 and 15 traits respectively. In a study with 51 genotypes, Palaniraja and Anbuselvam (2010) reported as many as 15 clusters for just seven traits.…”
Section: Genetic Diversity For Agro-morphological Traitsmentioning
confidence: 96%
“…Their genetic distances were 36.45 and 22.36 respectively. In six clusters Chakma et al, (2012) reported the highest genetic distance of 15.84 between clusters II and III. So also, Baradhan and Thangavel (2011) obtained a genetic distance of 13.2 between II and VI.…”
Section: Intra and Inter Cluster Distancesmentioning
confidence: 99%
“…In hybridization programs, parental lines must be selected from the clusters that are at highest genetic divergence because divergent parents are expected to produce wide variability and transgressive segregations with high heterotic effects [28,29]. Chakma et al [30] pointed out the role of the magnitude of genetic distance, the contribution of different characters towards the total divergence, and the magnitude of cluster mean for different characters performance in the selection of the parents for the hybridization program. Nisar et al [31] suggested selecting the lines belonging to diverse clusters and showing high mean performance in desirable directions for different traits can be used as parents in the breeding program.…”
Section: Mahalanobis Distancementioning
confidence: 99%